The Association between Oral Anticoagulants and Cancer Incidence among Individuals with Nonvalvular Atrial Fibrillation - Abrahami, Devin; Renoux, Christel; Yin, Hui; Fournier, Jean-Pascal; Azoulay, Laurent (Thrombosis and Haemostasis, 2020)
Objective Existing evidence on the association between vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs) and cancer is limited and contradictory. No observational studies have been conducted to simultaneously address the cancer safety of VKAs and DOACs. The objective of this study was to determine whether use of VKAs and DOACs, separately, when compared with nonuse, is associated with cancer overall and prespecified site-specific incidence.Methods Using the United Kingdom Clinical Practice Research Datalink, we identified patients newly diagnosed with nonvalvular atrial fibrillation (NVAF) between 2011 and 2017. Using a time-varying exposure definition, each person-day of follow-up was classified as use of (1) VKAs, (2) DOACs, (3) VKAs and DOACs (drug switchers), and (4) nonuse of anticoagulants (reference). We also conducted a head-to-head comparison of new users of DOACs versus VKAs using propensity score fine stratification weighting. Hazard ratios (HRs) with 95% confidence intervals (CIs) for cancer overall and prespecified subtypes were estimated using Cox proportional hazards models.Results Compared with nonuse, use of VKAs was not associated with cancer overall (HR: 1.05, 95% CI: 0.91–1.22) or cancer subtypes. Similarly, use of DOACs was not associated with cancer overall (HR: 1.13, 95% CI: 0.93–1.37), but an association was observed for colorectal cancer (HR: 1.73, 95% CI: 1.01–2.99), and pancreatic cancer generated an elevated, though nonsignificant HR (HR: 2.15, 95% CI: 0.72–6.44). Results were consistent in the head-to-head comparison.Conclusion Use of oral anticoagulants is not associated with the incidence of cancer overall among patients with NVAF. Possible associations between DOACs and colorectal and pancreatic cancer warrant further study.
Keywords: vitamin K antagonist; direct oral anticoagulant; cancer; population-based